2015
DOI: 10.1158/1078-0432.ccr-15-1185
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval: Palbociclib for the Treatment of Postmenopausal Patients with Estrogen Receptor–Positive, HER2-Negative Metastatic Breast Cancer

Abstract: On February 3, 2015, the FDA granted accelerated approval to palbociclib (IBRANCE, Pfizer Inc.), an inhibitor of cyclin-dependent kinases 4 and 6 (CDK4 and CDK6), for use in combination with letrozole for the treatment of postmenopausal women with estrogen receptor (ER)-positive, HER2-negative advanced breast cancer as initial endocrine-based therapy for their metastatic disease. The approval is based on a randomized, multicenter, open-label phase I/II trial (PALOMA-1) in 165 patients randomized to palbociclib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
189
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(205 citation statements)
references
References 9 publications
1
189
1
3
Order By: Relevance
“…[5][6][7][8][9][10][11] We analyzed the combinatorial effects of palbociclib with the commonly used chemotherapy agents against CRC, as a prelude to possible translation. Chou-Talalay analysis revealed that palbociclib can synergize with a variety of chemotherapies under hypoxia (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11] We analyzed the combinatorial effects of palbociclib with the commonly used chemotherapy agents against CRC, as a prelude to possible translation. Chou-Talalay analysis revealed that palbociclib can synergize with a variety of chemotherapies under hypoxia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Palbociclib was approved by the FDA in 2015 in combination with letrozole as initial hormone-plus CDK-targeted therapy for post-menopausal women with ER(C)/Her2(¡) advanced breast cancer. 5 The therapeutic effects of palbociclib have been demonstrated in numerous clinical trials for breast cancer, NSCLC, GBM, lymphoma, and leukemia, in combination with 5-FU and oxaliplatin in solid malignancies (NCT01522989) or with cetuximab in head and neck cancer. 6,7 A combined pharmacological inhibition of MEK and CDK4/6 led to substantial synergy in KRAS-mutated NSCLC in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 These studies have helped to motivate clinical trial evaluations of the CDK4/6 inhibitor (https://clinicaltrials.gov/ ct2/results?term=Palbociclib&Search=Search), one of which resulted in the recommended use of palbociclib with letrozole for treating postmenopausal women with estrogen receptorpositive, HER2-negative advanced breast cancer, as initial endocrine-based therapy for metastatic disease. 7 We previously determined that the amount of palbociclib present in intracranial GBM xenografts, following oral administration of the drug, was sufficient to achieve an antiproliferative effect. 5 Our GBM xenograft study also demonstrated superior antitumor activity when combining palbociclib with radiation as compared with either radiation or palbociclib monotherapy.…”
Section: Neuro-oncologymentioning
confidence: 99%
“…Given the activation of these growth-and survivalpromoting pathways after endocrine therapy, current clinical treatment strategies have begun combining endocrine-based agents with small-molecule inhibitors of these pathways (19,20). The increase in progression-free survival demonstrated in clinical studies such as BOLERO-2 and PALOMA-1 where an aromatase inhibitor was combined with everolimus (mTOR inhibitor) or palbociclib (CDK4/6 inhibitor), respectively, highlights the effectiveness of this strategy (21)(22)(23). Furthermore, recent data from the PALOMA-3 trial validate the use of a SERD (fulvestrant) in combination with CDK4/6 inhibitors as a potential new treatment strategy for metastatic disease (24).…”
Section: Introductionmentioning
confidence: 99%